Upaya Meningkatkan Hasil Belajar Materi Menceritakan Sejarah Indonesia Melalui Penerapan Metode Pembelajaran Word Square dan Scramble - Yonni Antoko (Departement of Mathematics Education, 2021)
This study aims to determine whether there is an increase in Learning Outcomes of Indonesian History Telling Materials through the application of Word Square and Scramble learning methods to 6th Grade students of SDN Medokan Ayu II/615 Surabaya, and to find out how much increase in Learning Outcomes of Indonesian History Telling Materials through the application of learning methods. Word Square and Scramble for Class 6 students at SDN Medokan Ayu II/615 Surabaya. Action research was carried out in two learning cycles by applying the Word Square and Scramble learning methods in Indonesian Language Subjects as the object of research. In the study, it was found that the authentic value and learning outcomes of students' storytelling history of Indonesia increased. This can be seen from the increase in students' learning outcomes of Telling Indonesian History from before this learning method was applied which only had an average of 53.8 to 71.3 in the first cycle and 77.7 in the second cycle. In addition, it was also found an increase in the percentage of classical completeness from cycle to cycle. Classical completeness in the first cycle was 59% with a moderately increasing category in the second cycle of 82% with a very good category. Based on the explanation of the results of the research and discussion, it can be concluded that there is an increase in Learning Outcomes of Indonesian History Telling Materials through the application of the Word Square and Scramble learning methods to the 6th grade students of SDN Medokan Ayu II/615 Surabaya.